Integrated management of alternaria leaf spot of cabbage (Brassica oleracea var. capitata (L.)) - Gunda V N S Madhu Kiran (Department of Plant Pathology, College of Agriculture, 2018)
The study entitled ‘Integrated management of Alternaria leaf spot of cabbage (Brassica oleracea var. capitata (L.))’ was performed in College of Agriculture, Vellayani during 2016-2018 with the objectives to study the leaf spot disease of cabbage caused by Alternaria spp. and to develop management strategy to control the disease using fungicides and biocontrol agents. As a part of study, survey was conducted in cabbage fields of three districts of Kerala viz., Trivandrum, Kollam and Idukki and the maximum per cent disease index (57.14%) was recorded in the cabbage fields of Muthuvankudy region in Idukki district. Seven isolates of Alternaria spp. were isolated and purified. Pathogenicity tests were conducted on the potted plants and the results revealed that the C6 isolated from Muthuvankudy of Idukki district was found to be most virulent and selected for further studies. Microscopic characters of different isolates of Alternaria spp. obtained during the survey were studied and showed that the mycelia were septate and conidia were produced in chains from the conidiophores. These conidia consist of both longitudinal and transverse septa and did not have beak which is the peculiar character of A. brassicicola. The morphological characters of C6 isolate were studied and the average conidial size ranged from 8-70 μm × 8-19 μm. The conidia were cylindrical in shape and did not have beak. Based on the molecular characterization of the C6 isolate through ITS sequencing, blast analysis in ClustalX2 software and dendrogram constructed using TreeView software confirmed as A. brassicicola with the reference number SR- 1058. Physiological studies were studied and determined the optimum temperature, pH and the light intensity for the growth of A. brassicicola. The optimum temperature for the growth of pathogen was 250C and the growth was less at 150C. which revealed that the harvested cabbage can be stored safely at the lower temperatures without any post-harvest damage. The maximum growth of the pathogen were recorded at pH 5.5 and 6. The fungi exposed under normal day and night condition showed maximum mycelial growth followed by dark and the growth and sporulation was declined with increase in the light intensity. The predominant fungal antagonists isolated from the phyllosphere of cabbage were Myrothecium sp, Penicillium sp. and a non sporulating fungus which exhibited 54.4%, 50% and 46% inhibition of the pathogen respectively under in vitro conditions. Molecular characterization of the most effective fungal antagonist was done with ITS sequencing and identified as M. inundatum with reference number SR-1082. The in vitro antagonism of five bioagents viz., Pseudomonas fluorescens (KAU), Trichoderma viride (KAU), T. harzianum (KAU), Bacillus subtilis (KAU) and M. inundatum were evaluated against the pathogen by dual culture technique and the results revealed that the maximum percentage inhibition was recorded with T. viride (82.2%) which was on par with T. harzianum (80%). The efficacy of fungicides were evaluated against A. brassicicola at three different concentrations viz., 0.05%, 0.1% and 0.2% concentrations with propiconazole, hexaconazole, tebuconazole, azoxystrobin and 0.1%, 0.2% and 0.4% concentrations with propineb, mancozeb, copper oxychloride by poisoned food technique and observed that four fungicides viz., propiconazole, hexaconazole, tebuconazole and copper oxychloride showed cent percent inhibition of pathogen at all the three concentrations. The compatibility of four effective fungicides viz., propiconazole, hexaconazole, tebuconazole (0.05%, 0.1%, 0.2%) and copper oxychloride (0.1%, 0.2% and 0.4%) were tested with the effective bioagents viz., T. viride, T. harzianum and B. subtilis by disc diffusion method and found that the triazole fungicides viz., propiconazole, hexaconazole and tebuconazole were found to be compatible with B. subtilis and incompatible with T. viride and T. harzianum at all the three concentrations under in vitro conditions. A pot culture study was undertaken with cabbage variety NS-183 and evaluated the efficacy of effective fungicides, bioagents and their compatible combination viz., propiconazole (0.05%), hexaconazole (0.05%), tebuconazole (0.05%), T.viride (106cfu/ml), T.harzianum (106cfu/ml), B.subtilis (108cfu/ml), hexaconazole (0.05%) + B.subtilis (106cfu/ml) against the Alternaria leaf spot of cabbage and the maximum disease suppression over control was recorded with combined spraying of hexacoazole + B. subtilis (79.4%) followed by hexaconazole (68.3%), tebuconazole (65.1%) and propiconazole (63.6%). Economic analysis on alternaria leaf spot of cabbage using fungicides, bioagents and their combination showed that maximum yield was recorded with hexaconazole + B. subtilis which was 29.5 q/ha. This was followed by hexaconazole (27.4 q/ha), tebuconazole (26.1 q/ha) and propiconazole (24.2/ha). Benefit cost ratio was assessed and showed that it was maximum with treatment hexaconazole + B. subtilis which was 2.09:1.0. This was followed by hexaconazole (2.02:1.0), tebuconazole (1.89:1.0) and propiconazole (1.76:1.0). The present study highlighted the importance of integrating hexaconazole with bioagent B. subtilis for effective management of Alternaria leaf spot of cabbage as it prevents the detrimental effects like development of resistance against a particular fungicide by the continuous use of the same fungicide under field conditions and for the long lasting protection even under storage conditions.